EDUKASI CLEAN INTERMITTENT CATHETERISATION (CIC) UNTUK MENCEGAH INFEKSI SALURAN KEMIH PADA PASIEN PEMAKAI KATETER JANGKA PANJANG - Ida Bagus Tatwa Yatindra; Anak Agung Sagung Mirah Prabandari; Kadek Cindy Mernika; Ni Wayan Yudi Wiarini; Ida Ayu Laksmi Paramita (JURNAL SEWAKA BHAKTI, 2023)
As life expectancy increases, there is more elderly population and incontinence cases that require long-term catheter. Long-term use of catheters can cause morbidity for patients, because they have to come to the hospital every 2 weeks on weekdays to change the catheter, thus compromising their work or if they are elderly who need to be accompanied by their families, it can burden their families. Improper catheter care can also cause urinary tract infections (UTIs). Therefore, a solution is needed. Clean intermittent catheterization (CIC) or also called self-catheterization can be a solution for this problem. The use of CIC can make patients do not have to carry tubes and catheter bags everywhere. Patients also do not need to change the catheter every 2 weeks, therefore are more efficient in terms of cost and time. We gave CIC education to long-term catheter users at the Urology Polyclinic of Tabanan Hospital using a urinary tract mannequin. The outcome revealed that all patient's post-test scores increased compared to the pre-test. The patients can apply CIC independently so that they no longer change catheters at the hospital, and no urinary tract infections occur based on urinalysis.